Sound Synthesis and Sampling, 3rd Edition - Russ, Martin (Routledge, 2012)
Sound Synthesis and Sampling' provides a comprehensive introduction to the underlying principles and practical techniques applied to both commercial and research sound synthesizers. This new edition has been updated throughout to reflect current needs and practices- revised and placed in a modern context, providing a guide to the theory of sound and sampling in the context of software and hardware that enables sound making. For the revised edition emphasis is on expanding explanations of software and computers, new sections include techniques for making sound physically, sections within analog and digital electronics. Martin Russ is well known and the book praised for its highly readable and non-mathematical approach making the subject accessible to readers starting out on computer music courses or those working in a studio.